Side Biases in Euro Banknotes Recognition: The Horizontal Mapping of Monetary Value - Giuliani, Felice; Manippa, Valerio; Brancucci, Alfredo; Tommasi, Luca; Pietroni, Davide (Frontiers in Psychology, 2018)
Money is a special stimulus for humans, because of its relevance in everyday life. However, the basic mechanisms underlying money representation have not been fully investigated yet. Left-right asymmetries in the visual perception and evaluation of monetary value offer such a possibility. In the present experiment, we tested the recognition of 5€ and 100€ banknotes presented in the left and right visual fields. Results show that the 100€ banknote is recognized faster than the 5€ banknote in the right visual field (RVF), while there is no difference in the left visual field (LVF). Our interpretation is that this effect is due to the matching between the positive valence conveyed by the 100€ banknote and the side in which it is mapped (right-positive). We consider this result as an evidence of a valence-based recognition of banknotes.